Skin conductance responses to masked emotional faces are modulated by hit rate but not signal detection theory adjustments for subjective differences in the detection threshold - Tsikandilakis, Myron; Chapman, Peter (SAGE, 2018)
The biological preparedness model has been interpreted to suggest that survival and social communication related visual cues can elicit physiological changes without awareness to enable us to instantly respond to our environment. Previous studies that tested this hypothesis using skin conductance have reported some evidence for physiological changes in response to masked emotional faces. In the current paper, we argue that this evidence is subject to possible methodological confounds. These include the use of a universal masked presentation threshold (e.g. 16.67 ms), the employment of possibly biased criteria such hit rates to measure meta-awareness and the assertion of overall guess-level target detection using non-significance. In the current report, we attempt to address these issues and test whether masked emotional faces can elicit changes in physiology. We present participants with subjectively adjusted masked angry, fearful, happy and neutral faces using hit rates and signal detection theory measures. We assess detection performance using a strict Bayesian criterion for guess-level target meta-awareness. Our findings reveal that hit rate adjustments in the detection threshold allow higher skin conductance responses to happy, fearful and angry faces but that this effect could not be reported by the same participants when the adjustments were made using unbiased signal detection measures. Combined these findings suggest that very brief biologically relevant stimuli can elicit physiological changes but cast doubt to the extent that this effect can occur in response to truly unconscious emotional faces.